The Washington manual rheumatology subspecialty consult - Kahl, Leslie E (Philadelphia : Wolters Kluwer Health/Lippincott Williams & Wilkins, 2012)
"The Washington Manual Subspecialty Consult Series is designed to provide quick access to the essential information needed to evaluate a patient on a subspecialty consult service - each manual has been completely reviewed, revised, and follows the format and template of The Washington Manual of Medical Therapeutics, 33/e. We believe the revised outline format will provide information in a more logical and readily accessible format. The content has been updated to reflect advancing technologies and therapeutics. The objective is for the reader to obtain a synopsis of symptoms, signs, and problems encountered in their daily workflow in a bulleted format for quick salient points. References to a more descriptive source have been provided, along with a second color to support quick access, and web resources for physicians and patients"--Provided by publisher
Includes bibliographical references and index
Keywords: Rheumatology -- Handbooks, manuals, etc; Rheumatism -- Handbooks, manuals, etc; Arthritis -- Handbooks, manuals, etc; Rheumatic Diseases -- diagnosis; Rheumatic Diseases -- therapy; Handbooks